2007
DOI: 10.1007/s11665-007-9176-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Advanced SPF Die Technologies in the Forming of a Production Panel

Abstract: Superplastic forming (SPF) is a manufacturing process that can facilitate increased use of aluminum in automobile body structures. Despite considerable advantages with regards to formability and tooling costs, the process has been mostly limited to low volume production due to relatively long cycle times and the need to use specially processed sheet alloys. To address these issues, advanced processes such as two stage gas forming (TSGF) and hot draw mechanical pre-forming (HDMP) have been developed. Advantages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Based on the two-stage SPF process, Luckey Jr. et al designed a preform die to improve the thickness profile of SPF5083 alloy parts [8]. Luo et al also compared two-stage gas forming (TSGF) and hot draw mechanical preforming (HDMP) to conventional SPF when forming a SPF5083 alloy part and found that HDMP could provide a superior thickness profile and faster forming cycle than the other two processes [9]. Liu et al combined deep drawing and blow forming into one operation.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the two-stage SPF process, Luckey Jr. et al designed a preform die to improve the thickness profile of SPF5083 alloy parts [8]. Luo et al also compared two-stage gas forming (TSGF) and hot draw mechanical preforming (HDMP) to conventional SPF when forming a SPF5083 alloy part and found that HDMP could provide a superior thickness profile and faster forming cycle than the other two processes [9]. Liu et al combined deep drawing and blow forming into one operation.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] This approach can reduce cycle time, thereby increasing possible production volumes. The simplest embodiment of this approach is either a plug-assist die or simply a die with a non-planar binder.…”
Section: Introductionmentioning
confidence: 99%
“…It has some advantages, such as forming large and complex work pieces, excellent precision and fine surface finish, and little springback or residual stress in the formed parts [2][3][4][5]. Conventional superplastic forming has been modified to increase the productivity and reduce some of the drawbacks, such as high percentage thinning to suit the automotive industries [6]. One of the modifications is to combine between the conventional SPF and the use of a non-superplastic AA5083 sheet [7].…”
Section: Introductionmentioning
confidence: 99%
“…The study of superplastic forming process mainly contains the material selection [8], processing technique [6], and finite element modeling (FEM) [9]. FEM is a numerical method normally used to facilitate the SPF process design [10].…”
Section: Introductionmentioning
confidence: 99%